Filipino Nursing Students' Challenges and Techniques in Learning Jargons - Aljon Delmo Galang; Elmer Santos De Guzman (Universitas Islam Negeri Alauddin Makassar, 2021)
Learning a jargon is indeed one of the most challenging facets in any field of specialization such as nursing, especially to novices. As they face this challenge, they tend to develop adaptive techniques vital in their studies. Nonetheless, being a practical source of learning experiences, identifying these challenges and techniques is significant to improve the edification process in the discipline. Hence, the study aims to narrate and analyze the challenges and techniques of fifteen (15) Filipino nursing student participants in learning jargons. This qualitative investigation used narrative research approach to retell the stories of the participants as they overcome the language demands of the nursing studies. Findings reveal that the challenges experienced by the participants are: (a) learning jargons, (b) word unfamiliarity, (c) schema insufficiency, and (d) their phonetic and orthographic perplexities. To address those, they read references, search on the Internet, and rely on memorization and familiarization through recall techniques and with nursing interlocutors. The empirical exploration was done to provide meaningful insights and inputs to clinical instruction through the lens of language learning, benefiting both instructors and students of nursing.